Towards a more efficient fracture care delivery by a public tertiary facility in the Philippines - Rosario, Mamer S.; Lantin, Ma. Loren Josephine O. (2020)
The intramedullary (IM) nails, donated by the non-profit organization SIGN Fracture Care International to the East Avenue Medical Center (EAMC), have allowed the facility to provide low-cost fracture care. However, the SIGN nails were provided selectively (selective SIGN nailing, or SSN) to indigent patients who are unable to come up with funds to procure commercial implants. Charity patients needing IM nail for fracture treatment are asked to settle the cost of a commercial implant, and only when a patient cannot provide the funds will he or she receive a SIGN nail. Therefore, it may take days or even weeks before it is decided that a patient can be treated using the donated implant. To expedite fracture care, upfront SIGN nailing (USN) for indicated cases has been strategized. Through USN, SIGN nails are provided to charity patients needing fracture care on a first-come-first-served basis, regardless of the patient’s financial capability. This article analyzes the efficiency of USN through mixed methods approach, utilizing focus group discussion (FGD) and analyses of surgery rate, SIGN utilization rate, and surgical timing from both USN and SSN policies. Themes elicited from the FGD emphasize USN’s pro-poor approach in improving surgical timing and expediting patient discharge. USN was also found to significantly improve surgery rate and surgical timing. However, the difference in SIGN nail use was found to be not significant, which may be due to a limitation of SIGN nail stocks at the EAMC. Therefore, the researchers conclude that performing USN surgeries demonstrates effective and efficient trauma care delivery despite an inadequate supply of SIGN nails.
Keywords: Orthopedic implants; Orthopedic surgery; Treatment of fractures; SIGN Fracture Care International; Health care delivery; Medical policy